2014
DOI: 10.1530/joe-14-0129
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between diet-induced obesity and chronic stress in mice: potential role of FKBP51

Abstract: While it is known that stress promotes obesity, the effects of stress within an obesogenic context are not so clear and molecular targets at the interface remain elusive. The FK506-binding protein 51 (FKBP51, gene: Fkbp5) has been identified as a target gene implicated in the development of stress-related psychiatric disorders and is a possible candidate for involvement in stress and metabolic regulation. The aims of the current study are to investigate the interaction between chronic stress and an obesogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 60 publications
4
38
1
Order By: Relevance
“…The CSDS paradigm lasted for 21 days and was conducted as described previously [23]. Briefly, experimental mice were placed in the cage of a male dominant aggressor (CD1) mouse.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CSDS paradigm lasted for 21 days and was conducted as described previously [23]. Briefly, experimental mice were placed in the cage of a male dominant aggressor (CD1) mouse.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, GR and FKBP51 are shown to program the persistent effects of early life experiences. In animal studies, it has been demonstrated that Nr3c1 and Fkbp5 gene expression are regulated by exposure to an HF diet during adulthood [22,23]. Taken together, the HPA axis and, in particular, GR and FKBP51 are prime candidates for linking maternal obesity and persistent behavioral changes in adult offspring.…”
Section: Introductionmentioning
confidence: 99%
“…In mice exposed to high-fat diet, Fkbp51 is induced in the ventromedial hypothalamic nuclei, in accordance with the hypothalamus being involved in the control of energy balance. 138 In contrast, under conditions of chronic stress, the expression of this IMM increases in the hippocampus, area of the brain involved in the response to stress. 138 Inasmuch as environmental stress is another risk factor for the development of obesity, 139 future studies are needed to uncover the role of FKBP51 in different areas of the brain, whether this IMM plays a role in the control of appetite and energy balance, and whether FKBP51 is implicated in the relationship between control of energy, metabolic homeostasis and stress response.…”
Section: Fkbp51 and Fkbp51 Knock Out Animal Modelsmentioning
confidence: 99%
“…In particular, we measured changes in epididymal white adipose tissue (eWAT) depots, based on previous findings demonstrating that they can be altered in different models of social stress [23,24]. Moreover, we evaluated interscapular brown adipose tissue (iBAT) and, using indirect calorimetry assay, we assessed energy expenditure and substrate oxidation (respiratory quotient, RQ).…”
Section: Introductionmentioning
confidence: 99%